Being your own Bae: writing within and against homonationalism in the short story cycle - Yam, Daryl Qilin (Nanyang Technological University, 2022)
In a 2014 TIME article about what the word "bae" means, computational linguist Tyler Schnoebelen explains: "'As it gets picked up by more people, its meaning will either calcify or bleach.' That is, harden into meaning only one very specific thing, or expand to embrace a range of meanings." Be Your Own Bae, my proposed title for the short story collection I'm working to complete, seeks to explicate via interconnected works of short fiction the tragicomic state of being queer and millennial in neoliberal, homonationalist Singapore, and how often this points towards a crisis of selfhood that demands more unique coping mechanisms in the journey towards self-fulfillment. Ultimately, the project aims to explore the forms of the short story and the short story cycle as creative strategies for queer worldbuilding, writing within and against homonationalism, demonstrated via the four stories included in this particular thesis. In the accompanying critical exegesis, I further aim to explore representations of homonationalist life in Singaporean short stories; present an analysis of short story cycles present in Singapore Literature; present attempts at queer worldbuilding found in Singapore short story collections; and finally, demonstrate how the three approaches combine and inform the writing of the above-mentioned four stories.